2008
DOI: 10.1007/s10658-008-9354-6
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, races, and host range of Aphanomyces euteiches from alfalfa production fields in the central USA

Abstract: Aphanomyces euteiches (races 1 and 2) causes root rot of alfalfa; however, its population biology and distribution are poorly understood where alfalfa is a major crop. The objectives of this study were to (1) characterise the distribution and frequency of races of A. euteiches in Illinois alfalfa fields, (2) determine host range of A. euteiches on cultivated and native legumes, and (iii) to describe genetic diversity and population genetic structure of A. euteiches in alfalfa fields. To accomplish this, soil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…A. euteiches is reported to attack other legume species including common bean, broad bean, faba bean, clover, and alfalfa (Pfender and Hagedorn, 1982 ; Lamari and Bernier, 1985 ; Tivoli et al, 2006 ; Moussart et al, 2008 ). In some regions of the United States, where pea and alfalfa crops were frequently included in cropping systems, populations of pea-infecting A. euteiches showed differentiation into sub-populations with differences in genotypes and virulence toward pea and alfalfa (Holub et al, 1991 ; Malvick et al, 1998 , 2009 ; Malvick and Grau, 2001 ). To investigate the presence of such distinct isolate genotypes, influenced by their host of origin in France, it would thus be necessary to increase the number of isolates sampled from the Bourgogne fields studied and from other fields with various legumes in their crop histories.…”
Section: Discussionmentioning
confidence: 99%
“…A. euteiches is reported to attack other legume species including common bean, broad bean, faba bean, clover, and alfalfa (Pfender and Hagedorn, 1982 ; Lamari and Bernier, 1985 ; Tivoli et al, 2006 ; Moussart et al, 2008 ). In some regions of the United States, where pea and alfalfa crops were frequently included in cropping systems, populations of pea-infecting A. euteiches showed differentiation into sub-populations with differences in genotypes and virulence toward pea and alfalfa (Holub et al, 1991 ; Malvick et al, 1998 , 2009 ; Malvick and Grau, 2001 ). To investigate the presence of such distinct isolate genotypes, influenced by their host of origin in France, it would thus be necessary to increase the number of isolates sampled from the Bourgogne fields studied and from other fields with various legumes in their crop histories.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the genetic architecture of QDR of M. truncatula seems to be governed by small-effect QDR loci in response to isolates Ae109, MF-1, and NC-1, which were reported to be pathogenic to a narrower host range, i.e., alfalfa and/or pea (Malvick et al 1998). The isolates Ae109, MF-1, and NC-1, originating from alfalfa production fields in the central United States (Malvick et al 2009), showed to be more adapted to M. truncatula, which is closely related to alfalfa, than the ATCC 201684 and RB84 isolates originating from pea growing areas in Europe.…”
Section: Truncatula Qdr Varies In Response To the Inoculated A Eumentioning
confidence: 99%
“…As suggested by Salt & Delanay (1985), the microflora or other biotic or abiotic soil factors may play an important role in root rot expression, and consequently could explain the lack of symptoms observed on alfalfa with naturally infested French soils. In contrast, aphanomyces root rot was reported in North American alfalfa fields, but the disease is due to specific isolates (Malvick et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%